The Rotterdam Rules : a South African perspective - Gordon, Goscelin Lucy (Rhodes University, Faculty of Law, Law, 2013)
The objective of this paper is to investigate the Rotterdam Rules, and to ascertain whether South Africa should accede to or ratify them. In order to accomplish this, South Africa's current maritime transport regime will be examined, and existing "problem areas" will be identified. This will be followed by a comparative analysis between the Rotterdam Rules and the Hague-Visby Rules, which South Africa applies as part of national law to regulate the carriage of goods by sea. As a new maritime Convention, the Rotterdam Rules have attracted widespread criticism and support, and whether such is justified will also be considered. Finally potential considerations South Africa should take into account in electing whether or not to accede or ratify the Rules have been assessed from a political, economic, social, technological, legal and environmental standpoint as at 31 December 2011
Keywords: Rotterdam Rules (2008); Contracts, Maritime; Maritime law; Maritime law -- South Africa